Quantitative accuracy improvement of laser-induced breakdown spectroscopy by a modified corner-cutting method for continuum background removal. Issue 12 (31st October 2022) - Hu, Zhenlin; Nie, Junfei; Chen, Feng; Zhang, Deng; Ouyang, Zhiyong; Liu, Yuanchao; Chu, Yanwu; Guo, Lianbo
Abstract : We proposed a modified corner-cutting method for continuum background removal in laser-induced breakdown spectroscopy. Abstract : As a popular elemental analysis technique, laser-induced breakdown spectroscopy (LIBS) has been applied in many fields, including coal analysis, nuclear industry, and deep-sea and Mars exploration. LIBS spectra have a continuum background (BG), which causes unsatisfactory analysis results, especially for calibration-free LIBS (CF-LIBS). In this work, we proposed a Moving-Average Corner-Cutting (MA-CC) method to remove BG in LIBS spectra. We compared MA-CC, Model-Free (MF), and Corner-Cutting (CC) methods by using simulated spectra, calibration curves of micro-alloyed steels, and CF-LIBS of a titanium alloy, respectively. For simulated spectra, MA-CC had the best performance in BG removal. For Ni I 345.85, Cr I 425.43, and Cu I 324.75/327.40 nm in micro-alloyed steels, the R 2 values of calibration curves were more than 0.99, higher than those from MF and CC. The mean relative error of CF-LIBS results from MA-CC was 2.21%, higher than 2.36% and 2.32% of MF and CC, respectively. The results showed that the MA-CC method had the highest robustness and improved the quantitative accuracy based on calibration curves and CF-LIBS, which is significant for the further application and popularization of LIBS.